Strategies to Improve the Quality of Arabic Language Education at the Public Service Entity (BLU) State Islamic Higher Education - Nurcholis, Ahmad; Muhajir, As'aril; Hidayatullah, Syaikhu Ihsan; Harianto, Budi; Arifuddin, Nur; Timbul, Timbul (Arabiyatuna: Jurnal Bahasa Arab, 2023)
The purposes of this study were to describe and analyze the strategies for improving the quality of Arabic language education in BLU State Islamic Higher Education at UIN SATU Tulungagung and UIN Maliki Malang. The main problem faced by BLU (Public Service Agency) organizers, including PTKIN (State Islamic Higher Education Institution) that has BLU status, is the lack of alignment in understanding among stakeholders. UIN SATU Tulungagung and UIN Maliki Malang have successfully implemented specific strategies in managing their BLU campuses. This qualitative study used theoretical orientation/perspective analysis method with a phenomenological approach. The strategies implemented in UIN SATU Tulungagung included: a) Forming a BLU acceleration unit, b) Funding for improving the quality of Arabic language education which came not only from UKT, and c) BLU UIN SATU Tulungagung supported the improvement of the quality of Arabic language education with a principle of not being profit oriented. The strategies implemented in UIN Maliki Malang consisted of three strategies: a) National Contribution, providing solutions to community problems while considering the priority of achieving UIN Maliki Malang's target criteria; b) International Reputation, accelerating the achievement of UIN Maliki Malang's target criteria as a research university and world-class university; and c) Organizational Transformation, ensuring the successful implementation of PKBLU by adhering to the principles of transparency, accountability, responsibility, independence, and fairness.